The additional impact of metabolic syndrome on left ventricular deformation and myocardial energetic efficiency impairment in ischemia with nonobstructive coronary arteries patients - Chen-Yan Min; Yue Gao; Yuan Li; Yi-Ning Jiang; Ying-Kun Guo; Hua-Yan Xu; Rong Xu; Xi Liu; Li-Ting Shen; Zhi-Gang Yang (Cardiovascular Diabetology)
Background Ischemia with nonobstructive coronary arteries (INOCA) has high morbidity, mortality, and poor quality of life. Metabolic syndrome (MetS) is a complex of multiple cardiac metabolic risk factors, significantly increasing the risk of major adverse cardiovascular events in INOCA patients. The study aimed to investigate the aggravating effect of MetS on left ventricular (LV) deformation and function impairment in INOCA patients. Materials and methods This study collected 104 INOCA patients (INOCA [MetS−]: n = 56; INOCA [MetS+]: n = 48) and 41 sex- and age-matched controls. LV function, indexed myocardial energetic efficiency (MEEI), and LV global peak strains (including radial, circumferential, and longitudinal directions) were measured among the three groups. The independent factors of reduced MEEI and impaired LV function and strain parameters for all INOCA patients were assessed using multivariable linear regression analyses. Results In contrast to the INOCA (MetS-) group, the indexed LV stroke volume (LVSVI) (49.57 ± 11.58 mL/m2 vs. 42.58 ± 12.23 mL/m2, p = 0.007), MEEI [0.85(0.70–1.03) ml/s/g vs. 0.75(0.54–0.91) ml/s/g, p = 0.045] and LV global longitudinal peak strain (GLPS) (− 13.26 ± 2.86% vs. -10.95 ± 3.93%, p = 0.001) reduced in the INOCA (MetS+) group. Compared with the controls, LV GLPS decreased in the INOCA (MetS-) group (− 15.14 ± 2.83% vs. −13.26 ± 2.86%, p = 0.017). MetS was negatively associated with LVSVI, MEEI, and LV GLPS (all p < 0.05). After multivariable adjustment, MetS was found to be an independent factor of decreased LVSVI (β = −0.231, p = 0.012), MEEI (β = −0.262, p = 0.009), and LV GLPS (β = −0.266, p = 0.002) in INOCA patients. Using calcium channel blockers medication (β = 0.320, p = 0.001) and hypertension (β = −0.298, p = 0.002) were also independently associated with impaired MEEI. Conclusions MetS aggravated LV deformation and function impairment in patients with INOCA. MetS was found to be an independent factor of impaired MEEI and LV GLPS, the further decrease of MEEI and LV GLPS in INOCA patients caused by MetS might involve the synergistic injury mechanism. Early diagnosis and treatment of MetS in patients with INOCA are important.